An Analysis of the Cost of Water Supply Linked to the Tourism Industry. An Application to the Case of the Island of Ibiza in Spain - González Pérez, Daniel María; Martín Martín, José María; Guaita Martínez, José Manuel; Sáez-Fernández, Francisco Javier (Water, 2021)
Tourist activity has a number of impacts on the destinations in which it takes place, among which are the environmental ones. A particular problem is the increase in water demand and wastewater production, which can compromise the balance of ecosystems. As many authors point out, there is a research gap in the comparative analysis between available water resources and the demand associated with tourism. In this respect, the main objective of this work is, on the one hand, to assess the water needs linked to the tourism industry and the capacity of natural resources to meet such a demand and, on the other hand, to estimate the economic cost of the water supply associated with the growing tourist demand in a territory, such as the island of Ibiza in Spain. It has been determined that the resources available are not sufficient to meet the water demand of the resident population at this destination, which is why it is necessary to resort to producing desalinated water. Therefore, the additional requirements associated with tourism must be met fully with desalinated water, which results in an increased cost of water management for the region. This paper also points at water losses in distribution networks and tourism seasonality as two phenomena that aggravate this issue.
Keywords: sustainable tourism; cost of desalination; environmental impacts; water management; JCR; Scopus